Low-light super-matt surface floor and method for manufacturing the same
Patent Information
- Application Number
- CN202511421166.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-09-30
AI Technical Summary
[0003]然而,传统地板的涂层经光固化后出现收缩较大,附着力差,防水性能不佳等问题,在长期使用中由于防水性能不足导致涂层在潮湿环境中易出现水渍渗透,不仅影响美观,更可能引发基材膨胀变形;同时带有涂层的地板一般光泽度高,虽然给人带来良好的视觉感受,但也带来光污染的问题,随着人们对生活品质要求的提高以及环保理念的深入人心,哑光表面的制品已越来越受欢迎
[0020] This invention utilizes the hydrolysis of tetraethyl orthosilicate to generate silica. A silica layer is then coated onto the surface of boron carbide using a sol-gel method to form a core-shell structure. After modification with a silane coupling agent (KH-570), the acrylate groups co-hydrolyze and condense with tetraethyl orthosilicate to generate a silicon-oxygen network grafted double bond structure. During UV curing, this structure chemically bonds with epoxy acrylate and polyurethane acrylate, forming a three-dimensional interpenetrating network. This significantly enhances the interfacial adhesion between the coating and the substrate. Furthermore, the nano-alumina effectively blocks moisture penetration pathways by filling micropores in the silicon-oxygen network, maintaining coating continuity and avoiding the film embrittlement problem caused by traditional matting agents.
Smart Images

Figure CN121022242B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flooring technology, and in particular to a low-gloss ultra-matte floor and its preparation method. Background Technology
[0002] With China's economic development and the continuous improvement of residents' living standards, flooring has gradually become the preferred material for floor decoration, and its market demand is showing a straight upward trend. However, flooring now requires maintenance to extend its service life, especially flooring in high-traffic areas. Therefore, to prevent wood flooring from wear and scratches, a layer of floor coating needs to be applied to the floor surface.
[0003] However, traditional floor coatings suffer from significant shrinkage, poor adhesion, and inadequate waterproofing after UV curing. Over long-term use, insufficient waterproofing can lead to water seepage in humid environments, affecting not only aesthetics but also potentially causing the substrate to swell and deform. Additionally, coated flooring typically has a high gloss level, which, while providing a pleasant visual experience, also contributes to light pollution. As people's demands for quality of life increase and environmental awareness grows, matte-finish products are becoming increasingly popular.
[0004] Current matte finish technologies mainly rely on silica-based additives. While these can reduce gloss, they can also lead to increased coating brittleness, decreased transparency, and reduced polishing resistance. Furthermore, traditional processes struggle to balance matte finish with waterproofing. Although the introduction of matte powder can improve the matte effect, it often disrupts coating continuity and actually exacerbates moisture penetration.
[0005] Therefore, how to develop a flooring that combines an ultra-matte finish, excellent waterproof performance, and good wear resistance has become a pressing technical problem for the industry. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a low-gloss ultra-matte floor and its preparation method.
[0007] A low-gloss ultra-matte flooring includes: a flooring substrate and a coating attached to the surface of the flooring substrate; the coating is formed by applying a substrate coating to the surface of the flooring substrate and then curing it with ultraviolet light.
[0008] The raw materials of the substrate coating, by weight, include: 20-40 parts epoxy acrylate, 20-40 parts polyurethane acrylate, 1-5 parts self-assembled block copolymer, 0.5-1.5 parts nano alumina, 10-20 parts tetraethyl orthosilicate, 1-5 parts boron carbide, 1-4 parts silane coupling agent, 1-2 parts photoinitiator, 5-15 parts reactive diluent, 1-2 parts defoamer, and 1-2 parts leveling agent.
[0009] Preferably, the self-assembled block copolymer is a polystyrene-polymethyl methacrylate block copolymer (PS-b-PMMA).
[0010] Preferably, the boron carbide has a mesh size of 400-500 mesh, and the nano-alumina has a particle size of 50-200 nm.
[0011] Preferably, the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone or / and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
[0012] Preferably, the reactive diluent is 1,6-hexanediol diacrylate or / and pentaerythritol triacrylate.
[0013] Preferably, the defoamer is BYK141 defoamer.
[0014] Preferably, the leveling agent is polyether-modified polydimethylsiloxane.
[0015] Preferably, the silane coupling agent is KH-570 coupling agent.
[0016] The preparation method of the above-mentioned low-gloss ultra-matte flooring includes the following steps: S1. Mix the reactive diluent, defoamer, and leveling agent to obtain a premix; S2. Add saturated ammonia to the ethanol aqueous solution until the pH of the system is 8-9. Add tetraethyl orthosilicate, boron carbide and silane coupling agent to it. Stir at 30-40℃ for 1-2 hours, heat to 70-80℃ and stir for 1-3 hours. Centrifuge, wash, vacuum dry and sieve to obtain composite powder. S3. Add epoxy acrylate, self-assembled block copolymer, composite powder and nano alumina to the premix and stir for 20-40 min. Add polyurethane acrylate and photoinitiator and stir for 5-10 min to obtain the substrate coating. S4. Apply the substrate coating to the surface of the floor substrate by roller coating and let it stand for 5-10 minutes before UV curing.
[0017] Preferably, in S4, the single-pass coating density is 10-15 g / m². 2 The total coating thickness is 0.3-0.5mm.
[0018] Preferably, in step S4, the specific operation of ultraviolet curing is as follows: irradiation with ultraviolet light at a wavelength of 365 nm, with an ultraviolet light irradiation energy density of 300-350 mJ / cm². 2 Irradiation was performed using ultraviolet light with a wavelength of 395 nm and an energy density of 400-450 mJ / cm². 2 .
[0019] Beneficial effects:
[0020] This invention utilizes the hydrolysis of tetraethyl orthosilicate to generate silica. A silica layer is then coated onto the surface of boron carbide using a sol-gel method to form a core-shell structure. After modification with a silane coupling agent (KH-570), the acrylate groups co-hydrolyze and condense with tetraethyl orthosilicate to generate a silicon-oxygen network grafted double bond structure. During UV curing, this structure chemically bonds with epoxy acrylate and polyurethane acrylate, forming a three-dimensional interpenetrating network. This significantly enhances the interfacial adhesion between the coating and the substrate. Furthermore, the nano-alumina effectively blocks moisture penetration pathways by filling micropores in the silicon-oxygen network, maintaining coating continuity and avoiding the film embrittlement problem caused by traditional matting agents.
[0021] The present invention achieves gradient crosslinking through staged UV curing by controlling wavelength and energy, which can effectively counteract shrinkage stress, reduce coating wrinkles, and further reduce the problem of decreased adhesion caused by shrinkage.
[0022] This invention utilizes the phase separation of PS-b-PMMA in the coating to form a microstructured interface layer. The micro-regions generate multiple scattering of incident light, significantly reducing surface gloss and effectively avoiding transparency loss. Combined with the composite powder, it forms a rough biomimetic interface similar to the "lotus leaf effect". The silicon-oxygen network provides low surface energy characteristics, which significantly improves the water contact angle, effectively blocking water stain penetration while providing excellent matte effect.
[0023] This invention achieves synergistic enhancement of waterproof performance and adhesion strength while maintaining an ultra-matte texture, and the preparation method is simple and suitable for large-scale application. Attached Figure Description
[0024] Figure 1 This is a comparison chart of the 60° mirror gloss and abrasion resistance of the flooring obtained in Example 5 and Comparative Examples 1-2.
[0025] Figure 2 The image shows a comparison of the static water contact angle and roll-off angle of the flooring obtained in Example 5 and Comparative Examples 1-2. Detailed Implementation
[0026] The present invention will be further explained below with reference to specific embodiments.
[0027] The bisphenol A epoxy acrylate resin used below was purchased from Shandong Mouhua Biotechnology Co., Ltd. The polyurethane acrylate used below was purchased from Hubei Mouyan Ligao Biomedical Co., Ltd., model 864 polyurethane acrylate. The PS-b-PMMA used below was purchased from Xi'an Mouxi Biotechnology Co., Ltd. The particle size of the nano-alumina used below was 120±20nm, and the boron carbide used below passed through a 450-mesh sieve. Example 1
[0028] A low-gloss ultra-matte flooring includes: a flooring substrate and a coating attached to the surface of the flooring substrate; the coating is formed by applying a substrate coating to the surface of the flooring substrate and then curing it with ultraviolet light.
[0029] The raw materials for the substrate coating include: 20g of bisphenol A epoxy acrylate resin, 20g of polyurethane acrylate, 1g of PS-b-PMMA, 0.5g of nano alumina, 10g of tetraethyl orthosilicate, 1g of boron carbide, 1g of KH-570 coupling agent, 1g of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 5g of 1,6-hexanediol diacrylate, 1g of BYK141 defoamer, and 1g of polyether-modified polydimethylsiloxane.
[0030] The preparation method of the above-mentioned low-gloss ultra-matte flooring includes the following steps: S1. Mix 1,6-hexanediol diacrylate, BYK141 defoamer, and polyether-modified polydimethylsiloxane, and stir at 1000 r / min for 5 min to obtain a premix. S2. Add saturated ammonia to 40g of 40% ethanol aqueous solution until the pH of the system is 8-9. Add tetraethyl orthosilicate, boron carbide and KH-570 coupling agent to the solution. Stir at 30℃ for 1h, then heat to 70℃ and stir for 1h. Centrifuge, wash, vacuum dry and pass through a 400-mesh sieve to obtain composite powder. S3. Add bisphenol A epoxy acrylate resin, PS-b-PMMA, composite powder and nano alumina to the premix and stir for 20 min. Add polyurethane acrylate and 2-hydroxy-2-methyl-1-phenyl-1-propanone and stir at 2000 r / min for 5 min to obtain the substrate coating. S4. Apply the substrate coating to the floor substrate surface using a roller coating method, with a single coat density of 10g / m². 2 The total coating thickness is 0.3 mm, and the coating is allowed to stand for 5 minutes after roller coating; ultraviolet light with a wavelength of 365 nm and an energy density of 300 mJ / cm² is then applied. 2 Irradiation was performed using ultraviolet light with a wavelength of 395 nm and an energy density of 400 mJ / cm². 2 . Example 2
[0031] A low-gloss ultra-matte flooring includes: a flooring substrate and a coating attached to the surface of the flooring substrate; the coating is formed by applying a substrate coating to the surface of the flooring substrate and then curing it with ultraviolet light.
[0032] The raw materials for the substrate coating include: 40g of bisphenol A epoxy acrylate resin, 40g of polyurethane acrylate, 3g of PS-b-PMMA, 1.5g of nano alumina, 20g of tetraethyl orthosilicate, 5g of boron carbide, 4g of KH-570 coupling agent, 2g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 15g of 1,6-hexanediol diacrylate, 2g of BYK141 defoamer, and 2g of polyether-modified polydimethylsiloxane.
[0033] The preparation method of the above-mentioned low-gloss ultra-matte flooring includes the following steps: S1. Mix 1,6-hexanediol diacrylate, BYK141 defoamer, and polyether-modified polydimethylsiloxane, and stir at 1500 r / min for 12 min to obtain a premix. S2. Add saturated ammonia to 60g of 60% ethanol aqueous solution until the pH of the system is 8-9. Add tetraethyl orthosilicate, boron carbide and KH-570 coupling agent to the solution. Stir at 40℃ for 2h, then heat to 80℃ and stir for 3h. Centrifuge, wash, vacuum dry and pass through a 400-mesh sieve to obtain composite powder. S3. Add bisphenol A epoxy acrylate resin, PS-b-PMMA, composite powder, and nano alumina to the premix and stir for 40 min. Add polyurethane acrylate and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide and stir at 3000 r / min for 10 min to obtain the substrate coating. S4. Apply the substrate coating to the floor substrate surface using a roller coating method, with a single coat density of 15g / m². 2 The total coating thickness is 0.5 mm, and the coating is allowed to stand for 10 minutes after roller coating; then it is irradiated with ultraviolet light with a wavelength of 365 nm and an ultraviolet light energy density of 350 mJ / cm². 2 Irradiation was performed using ultraviolet light with a wavelength of 395 nm and an energy density of 450 mJ / cm². 2 . Example 3
[0034] A low-gloss ultra-matte flooring includes: a flooring substrate and a coating attached to the surface of the flooring substrate; the coating is formed by applying a substrate coating to the surface of the flooring substrate and then curing it with ultraviolet light.
[0035] The raw materials for the substrate coating include: 25g of bisphenol A epoxy acrylate resin, 35g of polyurethane acrylate, 1.5g of PS-b-PMMA, 1.2g of nano-alumina, 12g of tetraethyl orthosilicate, 4g of boron carbide, 2g of KH-570 coupling agent, 1.3g of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 12g of pentaerythritol triacrylate, 1.3g of BYK141 defoamer, and 1.8g of polyether-modified polydimethylsiloxane.
[0036] The preparation method of the above-mentioned low-gloss ultra-matte flooring includes the following steps: S1. Mix pentaerythritol triacrylate, BYK141 defoamer, and polyether-modified polydimethylsiloxane, and stir at 1100 r / min for 10 min to obtain a premix. S2. Add saturated ammonia to 45g of 55% ethanol aqueous solution until the pH of the system is 8-9. Add tetraethyl orthosilicate, boron carbide and KH-570 coupling agent to the solution. Stir at 33℃ for 100min, then heat to 72℃ and stir for 2.5h. Centrifuge, wash, vacuum dry and pass through a 400-mesh sieve to obtain composite powder. S3. Add bisphenol A epoxy acrylate resin, PS-b-PMMA, composite powder and nano alumina to the premix and stir for 25 min. Add polyurethane acrylate and 2-hydroxy-2-methyl-1-phenyl-1-propanone and stir at 2800 r / min for 7 min to obtain the substrate coating. S4. Apply the substrate coating to the floor substrate surface using a roller coating method, with a single coat density of 13g / m². 2 The total coating thickness was 0.4 mm, and the coating was allowed to stand for 7 minutes after roller coating. Ultraviolet light with a wavelength of 365 nm and an energy density of 340 mJ / cm² was then applied. 2 Irradiation was performed using ultraviolet light with a wavelength of 395 nm and an energy density of 410 mJ / cm². 2 . Example 4
[0037] A low-gloss ultra-matte flooring includes: a flooring substrate and a coating attached to the surface of the flooring substrate; the coating is formed by applying a substrate coating to the surface of the flooring substrate and then curing it with ultraviolet light.
[0038] The raw materials for the substrate coating include: 35g of bisphenol A epoxy acrylate resin, 25g of polyurethane acrylate, 2.5g of PS-b-PMMA, 0.8g of nano alumina, 18g of tetraethyl orthosilicate, 2g of boron carbide, 3g of KH-570 coupling agent, 1.7g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 8g of pentaerythritol triacrylate, 1.7g of BYK141 defoamer, and 1.2g of polyether-modified polydimethylsiloxane.
[0039] The preparation method of the above-mentioned low-gloss ultra-matte flooring includes the following steps: S1. Mix pentaerythritol triacrylate, BYK141 defoamer, and polyether-modified polydimethylsiloxane, and stir at 1300 r / min for 6 min to obtain a premix. S2. Add saturated ammonia to 55g of 45% ethanol aqueous solution until the pH of the system is 8-9. Add tetraethyl orthosilicate, boron carbide and KH-570 coupling agent to the solution. Stir at 37℃ for 80min, then heat to 78℃ and stir for 1.5h. Centrifuge, wash, vacuum dry and pass through a 400-mesh sieve to obtain composite powder. S3. Add bisphenol A epoxy acrylate resin, PS-b-PMMA, composite powder and nano alumina to the premix and stir for 35 min. Add polyurethane acrylate and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide and stir at 2200 r / min for 9 min to obtain the substrate coating. S4. Apply the substrate coating to the floor substrate surface using a roller coating method, with a single coat density of 11 g / m². 2 The total coating thickness was 0.4 mm, and the coating was allowed to stand for 9 minutes after roller coating. Ultraviolet light with a wavelength of 365 nm and an energy density of 320 mJ / cm² was then applied. 2 Irradiation was performed using ultraviolet light with a wavelength of 395 nm and an energy density of 430 mJ / cm². 2 . Example 5
[0040] A low-gloss ultra-matte flooring includes: a flooring substrate and a coating attached to the surface of the flooring substrate; the coating is formed by applying a substrate coating to the surface of the flooring substrate and then curing it with ultraviolet light.
[0041] The raw materials for the substrate coating include: 30g of bisphenol A epoxy acrylate resin, 30g of polyurethane acrylate, 2g of PS-b-PMMA, 1g of nano alumina, 15g of tetraethyl orthosilicate, 3g of boron carbide, 2.5g of KH-570 coupling agent, 1.5g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 10g of 1,6-hexanediol diacrylate, 1.5g of BYK141 defoamer, and 1.5g of polyether-modified polydimethylsiloxane.
[0042] The preparation method of the above-mentioned low-gloss ultra-matte flooring includes the following steps: S1. Mix 1,6-hexanediol diacrylate, BYK141 defoamer, and polyether-modified polydimethylsiloxane, and stir at 1200 r / min for 8 min to obtain a premix. S2. Add saturated ammonia to 50g of 50% ethanol aqueous solution until the pH of the system is 8-9. Add tetraethyl orthosilicate, boron carbide and KH-570 coupling agent to the solution. Stir at 35℃ for 90min, then heat to 75℃ and stir for 2h. Centrifuge, wash, vacuum dry and pass through a 400-mesh sieve to obtain composite powder. S3. Add bisphenol A epoxy acrylate resin, PS-b-PMMA, composite powder and nano alumina to the premix and stir for 30 min. Add polyurethane acrylate and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide and stir at 2500 r / min for 8 min to obtain the substrate coating. S4. Apply the substrate coating to the floor substrate surface using a roller coating method, with a single coat density of 12g / m². 2 The total coating thickness was 0.4 mm, and the coating was allowed to stand for 8 minutes after roller coating. Ultraviolet light with a wavelength of 365 nm and an energy density of 330 mJ / cm² was then applied. 2 Irradiation was performed using ultraviolet light with a wavelength of 395 nm and an energy density of 420 mJ / cm². 2 .
[0043] Comparative Example 1 A low-gloss ultra-matte flooring includes: a flooring substrate and a coating attached to the surface of the flooring substrate; the coating is formed by applying a substrate coating to the surface of the flooring substrate and then curing it with ultraviolet light.
[0044] The raw materials for the substrate coating include: 30g of bisphenol A epoxy acrylate resin, 30g of polyurethane acrylate, 2g of PS-b-PMMA, 1g of nano alumina, 15g of tetraethyl orthosilicate, 3g of boron carbide, 2.5g of KH-570 coupling agent, 1.5g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 10g of 1,6-hexanediol diacrylate, 1.5g of BYK141 defoamer, and 1.5g of polyether-modified polydimethylsiloxane.
[0045] The preparation method of the above-mentioned low-gloss ultra-matte flooring includes the following steps: S1. Mix 1,6-hexanediol diacrylate, BYK141 defoamer, and polyether-modified polydimethylsiloxane, and stir at 1200 r / min for 8 min to obtain a premix. S2. Add saturated ammonia to 50g of 50% ethanol aqueous solution until the pH of the system is 8-9. Add tetraethyl orthosilicate and KH-570 coupling agent to the solution. Stir at 35℃ for 90min, then heat to 75℃ and stir for 2h. Centrifuge, wash, vacuum dry, add boron carbide, mix evenly, and pass through a 400-mesh sieve to obtain composite powder. S3. Add bisphenol A epoxy acrylate resin, PS-b-PMMA, composite powder and nano alumina to the premix and stir for 30 min. Add polyurethane acrylate and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide and stir at 2500 r / min for 8 min to obtain the substrate coating. S4. Apply the substrate coating to the floor substrate surface using a roller coating method, with a single coat density of 12g / m².2 The total coating thickness was 0.4 mm, and the coating was allowed to stand for 8 minutes after roller coating. Ultraviolet light with a wavelength of 365 nm and an energy density of 330 mJ / cm² was then applied. 2 Irradiation was performed using ultraviolet light with a wavelength of 395 nm and an energy density of 420 mJ / cm². 2 .
[0046] Comparative Example 2 A low-gloss ultra-matte flooring includes: a flooring substrate and a coating attached to the surface of the flooring substrate; the coating is formed by applying a substrate coating to the surface of the flooring substrate and then curing it with ultraviolet light.
[0047] The raw materials for the substrate coating include: 32g of bisphenol A epoxy acrylate resin, 30g of polyurethane acrylate, 1g of nano alumina, 15g of tetraethyl orthosilicate, 3g of boron carbide, 2.5g of KH-570 coupling agent, 1.5g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 10g of 1,6-hexanediol diacrylate, 1.5g of BYK141 defoamer, and 1.5g of polyether-modified polydimethylsiloxane.
[0048] The preparation method of the above-mentioned low-gloss ultra-matte flooring includes the following steps: S1. Mix 1,6-hexanediol diacrylate, BYK141 defoamer, and polyether-modified polydimethylsiloxane, and stir at 1200 r / min for 8 min to obtain a premix. S2. Add saturated ammonia to 50g of 50% ethanol aqueous solution until the pH of the system is 8-9. Add tetraethyl orthosilicate, boron carbide and KH-570 coupling agent to the solution. Stir at 35℃ for 90min, then heat to 75℃ and stir for 2h. Centrifuge, wash, vacuum dry and pass through a 400-mesh sieve to obtain composite powder. S3. Add bisphenol A epoxy acrylate resin, composite powder, and nano alumina to the premix and stir for 30 min. Then add polyurethane acrylate and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide and stir at 2500 r / min for 8 min to obtain the substrate coating. S4. Apply the substrate coating to the floor substrate surface using a roller coating method, with a single coat density of 12g / m². 2 The total coating thickness was 0.4 mm, and the coating was allowed to stand for 8 minutes after roller coating. Ultraviolet light with a wavelength of 365 nm and an energy density of 330 mJ / cm² was then applied. 2 Irradiation was performed using ultraviolet light with a wavelength of 395 nm and an energy density of 420 mJ / cm². 2 .
[0049] The 60° specular gloss of the floors obtained in Example 5 and Comparative Examples 1-2 was measured in accordance with GB / T 9754-2007 "Determination of 20°, 60° and 85° specular gloss of paint films without metallic pigments".
[0050] Referring to GB / T 1768-2006 "Determination of Abrasion Resistance of Paints and Varnishes - Rotary Rubber Grinding Wheel Method", the abrasion resistance of the floors obtained in Example 5 and Comparative Examples 1-2 was determined using a CS-10 rubber grinding wheel.
[0051] like Figure 1 As shown, the flooring obtained in Example 5 has the lowest 60° mirror gloss and the best matte effect, which is significantly better than Comparative Examples 1-2; while the flooring obtained in Example 5 has the lowest wear quality and the best wear resistance, which is significantly better than Comparative Examples 1-2.
[0052] The static water contact angle and roll-off angle of the floors obtained in Example 5 and Comparative Examples 1-2 were measured using a contact angle measuring instrument.
[0053] like Figure 2 As shown, the floor obtained in Example 5 has the largest static water contact angle and the smallest rolling angle, which is significantly better than that of Comparative Examples 1-2.
[0054] The hardness of the flooring obtained in Example 5 and Comparative Examples 1-2 was determined with reference to GB / T 6739-2022 "Determination of Hardness of Paints and Varnishes by Pencil Method"; and the adhesion of the flooring obtained in Example 5 and Comparative Examples 1-2 was determined with reference to GB / T 9286-2021 "Cross-cut Test of Paints and Varnishes".
[0055] In Example 5, the flooring obtained had a hardness of 7H and an adhesion grade of 0; in Comparative Example 1, the flooring obtained had a hardness of 5H and an adhesion grade of 1; and in Comparative Example 2, the flooring obtained had a hardness of 6H and an adhesion grade of 0.
[0056] The reason for the above results is that the present invention utilizes boron carbide and tetraethyl orthosilicate to coat the surface of boron carbide sheets with sol-gel to form a core-shell structure. After the surface is modified with silane coupling agent (KH-570), the acrylate groups and tetraethyl orthosilicate co-hydrolyze and condense to generate a silicon-oxygen network grafted double bond structure. During the UV curing process, it chemically bonds with epoxy acrylate and polyurethane acrylate to form a three-dimensional interpenetrating network. This not only significantly improves the interfacial bonding between the coating and the substrate, but also the nano-alumina effectively blocks the water penetration path by filling the micropore defects in the silicon-oxygen network and maintains the continuity of the coating, avoiding the film embrittlement problem caused by traditional matting powders. This invention utilizes the phase separation of PS-b-PMMA in the coating to form a microstructured interface layer. The microstructure generates multiple scattering of incident light, significantly reducing surface gloss and effectively avoiding transparency loss. Combined with the composite powder, it forms a rough biomimetic interface similar to the "lotus leaf effect". The silicon-oxygen network provides low surface energy characteristics, which significantly increases the water contact angle, effectively blocking water stain penetration while providing excellent matte effect.
[0057] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A low-gloss ultra-matte flooring, characterized in that, include: Floor substrate and coating applied to the surface of the floor substrate; The coating is formed by applying a base coating to the surface of the floor substrate and then curing it with ultraviolet light; The raw materials of the substrate coating, by weight, include: 20-40 parts epoxy acrylate, 20-40 parts polyurethane acrylate, 1-5 parts self-assembled block copolymer, 0.5-1.5 parts nano alumina, 10-20 parts tetraethyl orthosilicate, 1-5 parts boron carbide, 1-4 parts silane coupling agent, 1-2 parts photoinitiator, 5-15 parts reactive diluent, 1-2 parts defoamer, and 1-2 parts leveling agent; The self-assembled block copolymer is a polystyrene-polymethyl methacrylate block copolymer.
2. The low-gloss ultra-matte flooring according to claim 1, characterized in that, The boron carbide has a mesh size of 400-500 mesh, and the nano-alumina has a particle size of 50-200 nm.
3. The low-gloss ultra-matte flooring according to claim 1, characterized in that, The photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone or / and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
4. The low-gloss ultra-matte flooring according to claim 1, characterized in that, The reactive diluent is 1,6-hexanediol diacrylate or / and pentaerythritol triacrylate.
5. The low-gloss ultra-matte flooring according to claim 1, characterized in that, The defoamer is BYK141 defoamer.
6. The low-gloss ultra-matte flooring according to claim 1, characterized in that, The leveling agent is polyether-modified polydimethylsiloxane.
7. A method for preparing a low-gloss ultra-matte floor as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Mix the reactive diluent, defoamer, and leveling agent to obtain a premix; S2. Add saturated ammonia to the ethanol aqueous solution until the pH of the system is 8-9. Add tetraethyl orthosilicate, boron carbide and silane coupling agent to it. Stir at 30-40℃ for 1-2 hours, heat to 70-80℃ and stir for 1-3 hours. Centrifuge, wash, vacuum dry and sieve to obtain composite powder. S3. Add epoxy acrylate, self-assembled block copolymer, composite powder and nano alumina to the premix and stir for 20-40 min. Add polyurethane acrylate and photoinitiator and stir for 5-10 min to obtain the substrate coating. S4. Apply the substrate coating to the surface of the floor substrate by roller coating and let it stand for 5-10 minutes before UV curing.
8. The method for preparing the low-gloss ultra-matte flooring according to claim 7, characterized in that, In S4, the single-pass coating density is 40-60 g / m². 2 The total coating thickness is 0.3-0.5mm.
9. The method for preparing the low-gloss ultra-matte flooring according to claim 7, characterized in that, In S4, the specific operation of UV curing is as follows: UV light with a wavelength of 365nm is used for irradiation, and the UV light irradiation energy density is 300-350mJ / cm². 2 Irradiation was performed using ultraviolet light with a wavelength of 395 nm and an energy density of 400-450 mJ / cm². 2 .
Citation Information
Patent Citations
Organic-inorganic hybridization ultraviolet cured paint for protecting metallic surface
CN101307194A
Photocuring paint for wood and preparation method thereof
CN104893509A
Waterborne polyurethane matt topcoating and preparation method thereof
CN109233611A